2010
DOI: 10.1002/eji.201040797
|View full text |Cite
|
Sign up to set email alerts
|

Targeting SIRP‐α protects from type 2‐driven allergic airway inflammation

Abstract: The interplay between innate and adaptive immune responses is essential for the establishment of allergic diseases. CD47 and its receptor, signal regulatory protein a (SIRP-a), govern innate cell trafficking. We previously reported that administration of CD47 1/1 but not CD47 À/À SIRP-a 1 BM-derived DC (BMDC) induced airway inflammation and Th2 responses in otherwise resistant CD47-deficient mice. We show here that early administration of a CD47-Fc fusion molecule suppressed the accumulation of SIRP-a 1 DC in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
1
18
1
Order By: Relevance
“…In addition, it was reported that macrophages showed increased phagocytosis of cancer cells in the absence of CD47-mediated signaling (43). Interestingly, SIRP␣-Fc treatment interfering with the CD47 pathway was able to reduce Th2-driven allergic airway inflammation (44), a finding which is in line with the results of IgG2c dominant antibody responses in CD47KO mice after i.n. VLP vaccination.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In addition, it was reported that macrophages showed increased phagocytosis of cancer cells in the absence of CD47-mediated signaling (43). Interestingly, SIRP␣-Fc treatment interfering with the CD47 pathway was able to reduce Th2-driven allergic airway inflammation (44), a finding which is in line with the results of IgG2c dominant antibody responses in CD47KO mice after i.n. VLP vaccination.…”
Section: Discussionsupporting
confidence: 73%
“…Defective neutrophil migration was observed in the absence of CD47 expression (13). A deficiency or blockade of CD47 is protected from lipopolysaccharide (LPS)-induced acute inflammatory disease and Th2-driven airway inflammation by inhibiting the migration of leukocytes and neutrophils, respectively (44,47). However, in the present study, naive CD47KO mice showed higher or similar cellularity of neutrophils in the BALF and lungs compared to those in naive WT mice upon influenza virus infection, suggesting no defect in the migration of CD47-deficient neutrophils into the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…SIRP␣ proteolysis may modify numerous diseases where SIRP␣ signaling has been implicated including cancer (26), renal ischemia reperfusion injury (27), stroke (28), Crohn disease, (29), and allergic airway inflammation (30).…”
Section: Discussionmentioning
confidence: 99%
“…Blocking CD47 decreased macrophage and neutrophil recruitment into reperfused tissues and decreased ROS damage in these models. Consistent with an anti-inflammatory effect of CD47 blockade, administration of CD47-Fc suppressed the lymph node accumulation of SIRPα + dendritic cells, development of systemic and local Th2 responses, and airway inflammation in sensitized and challenged mice [127]. Similarly, administration of soluble SIRP-Fc as a decoy inhibited Langerhans cell migration to lymph nodes and the subsequent contact hypersensitivity upon re-challenge of the mice [128].…”
Section: Preclinical Therapeutic Applicationsmentioning
confidence: 92%